Messenger RNA profiling of human platelets by microarray hybridization - Bugert, Peter; Dugrillon, Alex; Günaydin, Ayse; Eichler, Hermann; Klüter, Harald (Thrombosis and Haemostasis, 2003)
Platelets are generally believed to be inactive in terms of de novo protein synthesis. On the other hand, the presence of ribosomes and mRNA molecules is well established. Many studies have used reverse transcriptase (RT) -PCR for detection of gene transcripts in platelets. As RT-PCR is a very sensitive method, any leukocyte contamination of platelet preparations can lead to false results. We performed three filtration procedures to minimize leukocyte contamination of pooled buffy-coat platelet concentrates prior to RNA isolation. Furthermore, by applying a genomic PCR approach with 50 amplification cycles we demonstrated that nucleated cells were not detectable. Microarray hybridization was used to analyze 9,850 individual human genes in RNA from purified platelets. In total we identified 1,526 (15.5%) positive genes. The data were confirmed in six individual experiments each performed on a PC pooled from four individual blood donations. Genes specific for nucleated blood cells such as CD4, CD83 and others were negative and verified the purity of PC. Overrepresentation of positive genes was found in the functional categories of glycoproteins/integrins (22.6% vs. 15.5%, p=0.029) and receptors (20.7% vs. 15.5%, p<0.001). Gene transcripts encoding RANTES, GRO-α, MIP-1α, MIP-1β, and others were found at high levels of signal intensity and confirmed literature data. This work provides a mRNA profile of human platelets and a complete list of results can be downloaded from the website of our institute www.ma.uni-heidelberg.de/inst/iti/plt_array.xls. The knowledge about gene transcripts may have an impact on the characterization of novel proteins and their functions in platelets.
Keywords: Gene transcripts; platelet transcriptome; leukocyte depletion